Prevalence and correlates of arthritis among a nationally representative population-based sample of older adults in India - Peltzer K. (2023)
This study aimed to determine the prevalence and correlates of self-reported arthritis in older adults in India. The crosssectional sample consisted of 52,393 individuals (≥50 years) from the Longitudinal Ageing Study in India (LASI) Wave 1 in 2017-2018. Results indicate that the prevalence of self-reported arthritis was 14.7%, 17.3% among women and 11.7% among men. In adjusted logistic regression analysis, older age, obesity, chronic lung disease, neurological or psychiatric problems, insomnia symptoms, hypertension, physical pain, gastrointestinal problems, periodontal disases and functional disability were positively associated with self-reported arthritis, while male sex was negatively associated with arthritis. In addition, in unadjusted analysis, physical inactivity, major depressive disorder, stroke, heart disease, angina, diabetes, high cholesterol, persistent headaches, and back pain or problems were positively, and married, high subjective socioeconomic status, current tobacco use and lifetime alcohol use were negatively associated with self-reported arthritis. One in seven older adults in India reported having been diagnosed with arthritis. Several risk factors were identified, which can be targeted in public health interventions.